Significant others and students' leisure-time physical activity intention: A prospective test of the social influence in sport model - Diana L.Y. Su; Alfred S.Y. Lee; Joan S.K. Chung; Tracy C.W. Tang; Catherine M. Capio; Lei Zhang; Derwin K.C. Chan (Elsevier, 2023)
Background/Objectives: This two-wave prospective study applied the Social Influence in Sport Model to investigate whether the social influences of parents, physical education (PE) teachers, and peers were predictive of students' intention to engage in leisure-time physical activity (PA). Methods: Participants were 2,484 secondary school students (11-18 years old) who completed a questionnaire assessing positive influence, punishment, and dysfunction from the three social agents (parents, PE teachers, and peers) at baseline, and PA intention at a 1-month follow-up. Structural equation modelling (SEM) yielded excellent goodness-of-fit and consistent pathways between the three social agents. Results: Students' leisure-time PA intention (R2 = .103 to 0.112) was positively associated with positive influence (β = .223 to 0.236, p < .001) and punishment (β = .214 to 0.256, p < .01), and negatively associated with dysfunction (β = - 0.281 to -.335, p < .001). Multi-group SEM showed that the predictions were invariant between parents, PE teachers, and peers. Furthermore, no significant differences in students' gender were found between perceived social influence and PA intention. Conclusion: The findings supported the application of the Social Influence in Sport Model in explaining the role of significant others on students' intention to take part in leisure-time PA.